2004
DOI: 10.1111/j.1447-0756.2004.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infection and correlation with cervical lesions in Japanese women

Abstract: Diagnosis of HPV infection is also important for the prediction of progression to CIN and cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Surprisingly, only 41% of HSIL samples showed single‐HPV type infections in the present study. In a previous Japanese study using a consensus primer‐based PCR assay and exfoliative cytology samples from CIN2‐3 cases, a single HPV type infection was found in 88.7% . In a study using GS‐31, 54% of CIN 2, 3 cases were shown to be infected with a single HPV type.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Surprisingly, only 41% of HSIL samples showed single‐HPV type infections in the present study. In a previous Japanese study using a consensus primer‐based PCR assay and exfoliative cytology samples from CIN2‐3 cases, a single HPV type infection was found in 88.7% . In a study using GS‐31, 54% of CIN 2, 3 cases were shown to be infected with a single HPV type.…”
Section: Discussionmentioning
confidence: 56%
“…Approximately 5‐15% of cervical cancer cases and a similar percentage of CIN3 were deemed HPV negative in previous studies . One possible explanation for these HPV‐negative cases is that an alternative TP53‐related pathway may induce malignant changes .…”
Section: Discussionmentioning
confidence: 97%
“…De SanJose reported the worldwide HPV prevalence via a meta‐analysis and found that the second peak of HPV prevalence in women after 44 years old presented with an area difference. For instance, in European and North American women, the HPV prevalence commonly declines after the age of 25 , while in Asian and Latin American women, the second rise in the HPV prevalence may emerge in some areas, such as China , Japan , Chile , Colombia , and Mexico . Some factors may be related to the second peak in the HPV prevalence, such as increased extramarital sexual behaviors of their husbands or themselves, or decreased immunity due to a female hormone decline during peri‐ or post‐menopause, which could lead to potential activation of HPV with a low replication status .…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of these conditions are HPV-positive; in some cases, the genome is only present in episomic or integrated form, in other cases, the complete virions are visible by electronic microscope [45,[60][61][62][63][64].…”
Section: Genital Potentially/overtly Malignant Lesions Hpv-relatedmentioning
confidence: 99%